ANALYSIS OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE AT THE POPULATION CONTROL OFFICE OF FAMILY PLANNING OF TEBING TINGGI CITY - Pohan, Hamsa Aulia; Rizky, M Chaerul (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
This research aims to analyze how much influence the work environment and work motivation have on employee performance with a total research sample of 30 people using a total sampling technique. The analysis technique used in this research is multiple linear regression assisted by the SPSS ver. 22.00. The results of this research show that the work environment has a significant and partial effect on employee performance with a t value of 3,211. Furthermore, work motivation has a significant and partial influence on employee performance with a t value of 4,472. Based on the results of research conducted by researchers, it shows that the work environment and work motivation simultaneously have a positive and significant influence on employee performance, where Fcount > Ftable, 10,736 > 3,354. The dominant factor in this research is work motivation as the main factor that influences employee performance.